Nonimaging optics - Winston, Roland; Minano, Juan C.; Benitez, Pablo, 1969-; Welford, W. T. (Amsterdam ; Boston, Mass. : Elsevier Academic Press, 2005)
From its inception nearly 30 years ago, the optical subdiscipline now referred to as nonimaging optics, has experienced dramatic growth. The term nonimaging optics is concerned with applications where imaging formation is not important but where effective and efficient collection, concentration, transport and distribution of light energy is - i.e. solar energy conversion, signal detection, illumination optics, measurement and testing. This book will incorporate the substantial developments of the past decade in this field. * Includes all substantial developments of the past decade in the rapidly moving field of nonimaging optics * The only authoritative reference on nonimaging optics, from the leader in the field.
Nonimaging optical systems and their uses -- Some basic ideas in geometrical optics -- Some designs of image-forming concentrators -- Nonimaging optical systems -- Developments and modifications of the compound parabolic concentrator -- The flow-line method for designing nonimaging optical systems -- Concentrators for prescribed irradiance -- Simultaneous multiple surface design method -- Imaging applications of nonimaging concentrators -- Consequences of symmetry -- Global optimization of high-performance concentrators -- A paradigm for a wave description of optical measurements -- Applications to solar energy concentration -- Manufacturing tolerances.
Successor to: High collection nonimaging optics / W.T. Welford, R. Winston.
Includes bibliographical references and index.
Keywords: Solar collectors; Optics; Reflectors, Lighting; Electronic books